Feasibility studies of intraocular use of gelatin methacryloyl hydrogel to patch retinal tears. (18th April 2021) - Chen, Juan; Wang, Chunyi; Wen, Wen; Ni, Jie; Jiang, Jingjie; Ge, Zhongjun; Wang, Mingwei; Zhang, Fang
Absract: We engineered gelatin methacryloyl (GelMA) to be a sealant that can patch retinal tears and verified its biocompatibility in rabbit eyes. We compared adhesion, stability at 37°C, degradation time, swelling ratio, photo‐crosslinking time, pH, and physical conditions before photo‐crosslinking GelMA at 37°C with different methacrylic anhydride (MA) degrees of substitution (25, 50, and 75%) and concentrations (10, 20, and 30%). We injected 0.1 ml GelMA prepolymer into the vitreous cavity in study rabbits ( n = 6) and 0.1 ml normal saline into control rabbits ( n = 6), and performed clinical and histological examinations. GelMA hydrogel with a 75% degree of substitution and 20% concentration (75/20) exhibited stronger adhesion and stable properties during the first 2 weeks. It can be injected with a 25‐gauge needle at 37°C before photo‐crosslinking. Degradation time was acceptable, the swelling ratio was low, photo‐crosslinking time was short, and the pH was stable. No significant inflammation or other complications occurred, and intraocular pressure remained within a normal range of 16–20 mmHg after surgery. Histological examination revealed no damage to the retinal layers. GelMA (75/20) was the most suitable formulation to close retinal tears, and it exhibited satisfactory intraocular biocompatibility. GelMA can be used as a patch to seal retinal tears during vitrectomy for rhegmatogenous retinal detachment.